THE INFLUENCE OF THE THERMAL REDUCTION TEMPERATURE ON THE STRUCTURE AND ELECTROPHYSICAL PROPERTIES OF REDUCED GRAPHENE OXIDE FILMS - Denis Yu. Kornilov (Известия высших учебных заведений России: Радиоэлектроника, 2019)
Introduction. An incomplete list of graphene properties includes high electric conductivity, thermal conductivity, strength, large surface area, high light transmittance. Graphene is a very promising material from the point of view of its application in micro- and nanoelectronics. In addition, graphene advantage is a possibility of its obtaining by various ways. It allows creating materials with desired physicochemical properties by using appropriate technological methods. Objective. The investigation of a thermal reduction temperature influence on physicochemical properties of graphene oxide (GO) films. Materials and methods. In the present work, GO films are obtained on a slide surface by its immersing and removing from a graphene oxide water dispersion (dip coating). Obtained samples are studied by methods of scanning electron microscopy, Raman spectroscopy, and elemental CHN analysis. A sheet resistance is measured by a four-point probes method. Results. A content difference of elements (C, H, N) in studied samples, and both graphene structure defectiveness and sheet resistance decrease, are found to be proportional to a reduction temperature increase. A GO films thickness decrease during a heat treatment is also observed, which is presumably associated with a functional GO groups loss while thermal reduction. Conclusion. Research results demonstrate a possibility of a carbon films with desired physicochemical properties obtaining from a reduced graphene oxide (RGO), which can be used in thin-film technologies. Presented materials can also be useful in issues related to GO and RGO obtaining and applying.